2018
DOI: 10.1136/gutjnl-2017-315909
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the investigation of chronic diarrhoea in adults: British Society of Gastroenterology, 3rd edition

Abstract: Chronic diarrhoea is a common problem, hence clear guidance on investigations is required. This is an updated guideline from 2003 for the investigations of chronic diarrhoea commissioned by the Clinical Services and Standards Committee of the British Society of Gastroenterology (BSG). This document has undergone significant revision in content through input by 13 members of the Guideline Development Group (GDG) representing various institutions. The GRADE system was used to appraise the quality of evidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
242
0
36

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(285 citation statements)
references
References 228 publications
7
242
0
36
Order By: Relevance
“…BAM is a frequently overlooked condition in patients with ongoing episodes of loose stool 8. Our study has shown the cost saving benefits of performing tests for BAM/BAD first line with a median saving of more than £750 compared with performing it later on.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…BAM is a frequently overlooked condition in patients with ongoing episodes of loose stool 8. Our study has shown the cost saving benefits of performing tests for BAM/BAD first line with a median saving of more than £750 compared with performing it later on.…”
Section: Discussionmentioning
confidence: 70%
“…Formal testing is now the diagnostic approach recommended 8. This seems entirely reasonable as it has become clearer that empirical therapy does not always give clear-cut results,34 and this may contribute to the large group of patients with BAM/BAD who have had their diagnosis missed repeatedly, the so-called ‘revolving door’ effect where people with IBS-like symptoms have repeated referrals and investigations but do not respond to treatments offered 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the UK, a recent audit suggests that access to, and standardization of, scanning remains an issue, although referrals are increasing . Recently revised guidelines for the management of chronic diarrhea from the British Society of Gastroenterology recommend SeHCAT scanning should be performed in patients with chronic diarrhea referred to secondary care, and data suggest that earlier use of SeHCAT scanning results in fewer subsequent investigations in patients with chronic diarrhea . However, the test is under‐utilized, even in centers where it is available, which may reflect the preference of some clinicians to undertake a therapeutic trial of a bile acid sequestrant instead.…”
Section: Introductionmentioning
confidence: 99%
“…However, we continued to encourage its use in all other patients with chronic diarrhea because of the high yield of the test overall. This approach has since been supported by revised UK national guidance . The aims of the current study were therefore to assess whether yield of SeHCAT scanning had decreased subsequently, to re‐examine factors that predicted a positive test, and to reassess characteristics of patients with BAD according to both type and severity.…”
Section: Introductionmentioning
confidence: 99%